Understanding Women’s Help-Seeking With Intimate Partner Violence in Tanzania - Mahenge, Bathsheba (Violence against women, 2021)
Intimate partner violence (IPV) is a serious global health problem affecting millions of women worldwide. Despite increased investments into its reduction, little research has been conducted into how women in low- and middle-income countries deal with IPV. This study seeks to explore this by looking in depth into help-seeking strategies utilized by abused women in Tanzania, using the 2015–2016 Tanzania Demographic and Health Survey. The prevalence of lifetime physical and/or sexual IPV was 41.6% in this study, but only half of all affected women sought help from anyone. The only clear association found with help-seeking was the severity of IPV.